Sharp bounds of the third Hankel determinant for classes of univalent functions with bounded turning - Obradović, Milutin; Tuneski, Nikola; Zaprawa, Paweł (Institute of Mathematics, Czech Academy of Sciences, 2022)
We improve the bounds of the third order Hankel determinant for two classes of univalent functions with bounded turning.
Keywords: analytic function; univalent function; Hankel determinant; upper bound; bounded turning